Cisco firewall technology - Mason, Andrew (Cisco Press, 2007)
Cisco Firewall Technologies (Digital Short Cut) Andrew Mason ISBN-10: 1-58705-329-2 ISBN-13: 978-1-58705-329-0 Cisco Firewall Technologies provides you with a no-nonsense, easy-to-read guide to different types of firewall technologies along with information on how these technologies are represented in the Cisco® firewall product family. The main Cisco products covered are the IOS® Firewall, the PIX® Firewall, and the ASA. The majority of focus for the Short Cut will be on the ASA and emphasis will be placed upon the latest functionality released in version 7.2. The Short Cut also provides a walkthrough for configuring the ASA using the Adaptive Security Device Manager (ASDM), the GUI management and configuration tool provided with the ASA. The Short Cut presents you with the background information and product knowledge to make qualified decisions about the type of firewall technology that best fits your working environment. This is a Cisco technology focused Short Cut, so the emphasis will be solely on Cisco firewall products. Table of Contents: Chapter 1: Firewall Technologies Chapter 2: Cisco Firewall Technologies Chapter 3: Advancements in the ASA About the Author: Andrew Mason, CCIE® No. 7144, is a networking and security consultant based in the UK. He holds various industry certifications including CCIE, CISSP, and CEH. Andrew has 15 years experience in the IT industry, working in Internet security for the past several. He is involved daily in the design and implementation of security deployments for numerous clients based upon Cisco technology. About the Technical Editor: David Hucaby, CCIE No. 4594, is a lead network engineer for the University of Kentucky, where he works with healthcare networks based on the Cisco Catalyst®, ASA/PIX/FWSM security, and VPN product lines. David was one of the beta reviewers of the PIX Firewall 7.0 operating system software. David has a B.S. and M.S. in electrical engineering from the University of Kentucky and has worked in the IT field for 19 years. He lives in Kentucky with his wife Marci and two daughters.